2011
DOI: 10.1111/j.1526-100x.2011.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Ecosystems Around the Mediterranean Basin: Beyond the Frontiers of Ecological Science

Abstract: Based on concrete examples gathered from the Mediterranean region, this article shows why restoration ecology around the Mediterranean Basin must go beyond ecological science to embrace a contrasting local vision which integrates social and political realities. By taking into account the growing gap between the northern and southern/eastern shores of the Mediterranean, we propose the adoption of a double agenda for restoration around the Mediterranean to overcome the fact that restoration objectives are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In ecological restoration, both formal and local knowledge are complementary, and their combination can be beneficial for sustaining the delivery of multiple ecosystem services (Khater et al, 2012). In this sense, our results showed that each group is called to learn from the other in order to capture the entire range of ecological restoration targets.…”
Section: Implications For Ecological Restorationmentioning
confidence: 82%
See 1 more Smart Citation
“…In ecological restoration, both formal and local knowledge are complementary, and their combination can be beneficial for sustaining the delivery of multiple ecosystem services (Khater et al, 2012). In this sense, our results showed that each group is called to learn from the other in order to capture the entire range of ecological restoration targets.…”
Section: Implications For Ecological Restorationmentioning
confidence: 82%
“…Furthermore, their opinion is rarely considered in the early phases of the projects, such as the definition of objectives and priorities of restoration actions (Khater et al, 2012). In most cases, scientists and managers seem more concerned about the acceptance of their own visions, rather than open to the perspectives and needs of other stakeholders (Menzel and Teng, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is considered a basic element supporting the restoration process of Mediterranean areas (Khater et al 2011). Public has been informed about the need and the aims of the restoration effort and its success has a positive effect on people, in total agreement with the so-called "socially robust restoration strategies" (Gross 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the last decades, Lebanon faced intense quarrying activities resulting in severe degradation of its ecosystems, illustrated by alterations of the vegetation cover, landform modifications and natural resources' depletion (Khater et al, 2011a;2011b). The number of quarries in Lebanon increased from 784 to 1278 between 1989 and 2005, and quarried areas almost doubled since then (Darwish et al, 2011).…”
Section: A Importance and Impacts Of Quarriesmentioning
confidence: 99%
“…Ideally, restoration ecology provides clear concepts, models, methodologies and tools for practitioners to support their practice . The practice of restoration ecology, when dealing with a degraded ecosystem, offers three ways for accelerating and orienting the natural processes (Khater et al, 2011b). Aronson et al (1993), Aronson and Le Floc'h (1995), Martin et al (2002), SER (2002, and offer an exhaustive review of these three main concepts' definitions which could be restated as: 1) Restoration: relying on spontaneous natural processes/dynamics and assisting the recovery of the pre-existing ecosystem (closer to what it was before the anthropic disturbance).…”
Section: B Quarries: a Promising Scarmentioning
confidence: 99%